Efectos jurídicos de la inexistencias de garantías del uso efectivo de la pensión alimenticia de los niños, niñas y adolescentes en el cantón Pasaje, provincia de El Oro, en el periodo 2012-2013, propuesta de reforma: capitulo III agregado al título V, libro II del código de la niñez y la adolescencia. - Pérez Montaño, Ángel Leiví (2013)
This thesis points out with a teleological approach the existing legal anomie in law food of children and adolescents, since in practice all established legal procedure focuses on the collection of pension, despite the constitutional principles such as best interests of the children are guaranteed ultima ratio to ensure the effective use of these values for their owners. The main objective is to determine the legal consequences arising from this problem. The thesis is divided into four chapters, the first performs a current description of the problem, pointing out possible causes and effects, and their respective justification and systematizing the identification of the most relevant to the present objectives and hypotheses aspects.